Psychopathic Traits and Their Association with Adjustment Problems in Girls - Charles, Nora E. (2012)
RATIONALE: Psychopathic traits, and specifically callous-unemotional (CU) traits, are associated with a variety of adverse outcomes in adolescence and adulthood. The majority of research in this area has focused on men and boys, though there is some evidence that psychopathy is expressed differently in girls and women. OBJECTIVES: The purpose of this study was to test if the relationships of callous-unemotional (CU) traits with adjustment differed between girls and boys at risk for antisocial behavior. METHODS: Children whose biological father had past or current alcohol or drug problems were recruited for this research. A total of 234 children (116 boys, 118 girls; ages 10–12) were rated by their parent or guardian on CU traits and overall adjustment. RESULTS: Boys were generally rated higher on measures of CU traits; however, these traits were more prominently related to adjustment problems among girls. CONCLUSIONS: These results suggest that expression of psychopathic traits may have more negative effects on adjustment for girls than boys. One possible mechanism by which CU traits could be impacting adjustment in girls is by impairing interpersonal relationships.